The production of animal feed in the Ethiopian highlands: Potentials and limitations - Jutzi, S.C.; Haque, I.; Tedla, A. (Institute of Agricultural Research, 1987)
Reports on research activities carried out by ILCA's highland programme to devise an appropriate animal feed production strategy for small scale farmeres in the Ethiopian highlands. Gives a critical analysis of the available sources of animal feed, such as, roughages from native pasture, browse and crop residues. Assesses feed production technologies and improved animal based management of vertisols for increased grain and feed production.